Atom probe tomography analysis of InAlGaAs capped InAs/GaAs stacked quantum dots with variable barrier layer thickness. (15th January 2016) - Hernández-Saz, J.; Herrera, M.; Molina, S.I.; Stanley, C.R.; Duguay, S.
Abstract: In this work, we analyse by Atom Probe Tomography (APT) the composition distribution of InAs/GaAs stacked quantum dots (QDs) with InAlGaAs capping layers. Two different GaAs barrier layer thicknesses have been considered, 20 nm and 30 nm. Our results have shown the vertical alignment of QDs in the structure with reduced barrier layer and the unexpected formation of InGaAs quantum rings (QRings) surrounded by an Al-rich area in this sample. The APT data show that the QRings contain an amount of In atoms that is double the In composition in the QDs. The reduced strain measured in the QRings with regard to the QDs suggests that this change in morphology is promoted by the reduction in the strain of the nanostructure. The behaviour of Al during the process of formation of the QRings is also discussed. Graphical abstract: